The emancipatory city? : paradoxes and possibilities - Lees, Loretta (Sage Publications, 2004)
The Emancipatory City is a wonderful addition to a growing literature on the public culture of the city. In these spaces, tolerance and intolerance, difference and indifference, transgressions, resistances, and playful spontaneity erupt to give texture to urban life. The book broadens our gaze and deepens our understanding of how cities enable people to express themselves and be free' - Robert A Beauregard, New School University, New York Who are cities for? What kinds of societies might they most democratically embody? And, how can cities be emancipatory sites? The ambivalent status of urban space in terms of emancipation, democratisation, justice and citizenship is central to recent work in urban geography, 'new' cultural geography, critical geography and postmodern planning, as well as literature on urban social justice, public space and the politics of identity. Seeking alternative and progressive visions of the emancipatory city through an exploration of the tensions and possibilities between the freedoms and constraints offered by the city, the authors of The Emancipatory City? build on this wealth of current perspectives to present an critical analysis of urban experience.